Towards a unified regional surveillance system: the Gulf CDC’s first initiatives - Sami Al Mudarra; Lamis Alghamdi; Ahmed AlHatlan; Andrew Amato Gauci; Aleksandra Polkowska Kramek; Alaa Alqurashi; Nouf Alzuhayri; Sadeem AlShiban; Bushra Alghamdi; Pasi Penttinen (Frontiers in Public Health)
In January 2021, the Gulf Health Council (GHC), established the Gulf Centre for Disease Prevention and Control (Gulf CDC) in Riyadh, marking a pivotal step in harmonizing health strategies, enhancing knowledge generation, and promoting evidence-based approaches to both communicable (CD) and non-communicable diseases (NCD). The Gulf CDC’s mission includes consolidating the region’s health information systems, crucial for monitoring disease burden and shaping effective public health policies. An initial assessment of public health surveillance systems across the Gulf Cooperation Council (GCC) member states was conducted by the Gulf CDC. This revealed strong national surveillance coverage of CDs but identified areas for improvement, particularly in data quality and representativeness. These findings informed the development of the Gulf CDC’s health information strategy and confirmed the need for a regional surveillance system. Prior to the introduction of this system, senior experts in this field from all GCC member states were surveyed and a consensus process launched to agree on the first steps. This led to the strategic selection of a small number of priority communicable and non-communicable diseases for the pilot phase of the system. The final agreed list of diseases and conditions for the pilot are the CDs: acute respiratory infection (ARI), endemic dengue, brucellosis, measles and pulmonary tuberculosis together with the NCDs: cancer (registry) and road traffic injuries. The initiative will showcase the potential benefits of regional collaboration to improve health outcomes and will ultimately also contribute to global health security efforts.